KOLABORASI GURU-DOSEN DALAM PENELITIAN TINDAKAN KELAS UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Sukatiman Sukatiman; Roemintoyo Roemintoyo; Chundakus H; M. Akhyar; Sutikno Sutikno; Suwarno Suwarno (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2020)
Lecturers have broad autonomy in developing instructional. With the characteristics possessed by these lecturers, collaboration between lecturers (team teaching) is a challenge that is sometimes not easy. However, in vocational learning, lecturer cooperation in learning is something that cannot be avoided. In the Classroom Action Research to SMK, researchers collaborated at partner schools of SMKN 5 Surakarta and SMKN I Mondokan Sragen. The type of research used is ethnographic research, which is a qualitative observation method used in social science that focuses on field studies and their interactions, and sees everything as unique. The method used in conducting the evaluation is the equivalent test, which is a test that aims to measure its reliability identically with the reference test. The conclusion that can be drawn in this PDS program is to complement each other's strengths and weaknesses in organizing the learning process for SMK. Pamong teachers who work together are senior teachers who have eaten a lot of salt in their teaching. Pamong teachers have adequate competence in teaching and educating students, on the other hand, senior teachers have limitations in developing learning innovations. This is where the role of PDS lecturers in completing the shortage of teachers. The innovation that the lecturers did was to provide guidance using e-learning in learning at SMK. This e-learning has many advantages in learning the millennial generation. By maintaining student motivation, the learning objectives will be better achieved.